La capacidad de respuesta de América Latina ante la crisis - Betancourt, Belisario (Estudios Internacionales, 1983)
This paper analyzes one of the most difficult situations in the economic history of Latin America and the world and attempts to answer five great questions: What are the causes of the current international recession and how does the intensity and nature compare with previous cycles?; To what extent are the problems of developing countries caused by external factors and what responsibility does the implementation of internal policies have? In the specific case of Latin America, does the region have sufficient response capacity or is it bankrupt? ; What should be the basic ingredients of a global reactivation strategy that harmonizes the interests of developing, socialist and highly industrialized countries? And, finally, to what extent do the positive signs of recovery in the North American economy anticipate a new upward cycle in the international economy or is it more of a transitory reactivation?